Study on the prevalence and incidence of urolithiasis in Germany comparing the years 1979 vs. 2000 - Hesse, Albrecht; Brändle, Edgar; Wilbert, Dirk; Köhrmann, Kai-Uwe; Alken, Peter (European urology, 2003)
Objectives: In 1979, we conducted a representative study to determine the prevalence and incidence of urolithiasis in Germany. Significant progress in stone therapy and changes in nutritional and environmental factors since then consequently led to a second study in 2001 under the same conditions as in 1979. Methods: A representative sample of 7500 persons from all over Germany was questioned on the occurrence of urinary stones during their lifetimes (prevalence) and on acute urolithiasis in 2000 (incidence). Additionally, data were collected on urinary stone therapy and metaphylaxis. The current data were then compared with those from 1979. Results: Prevalence has risen from 4% to 4.7% from 1979 to 2001. 9.7% of the 50-64 year old males in 2000 had already had urinary stones (females: 5.9%). The current recurrence rate of urinary stones was estimated to be 42%. In the year 2000, the incidence of urolithiasis in Germany was found to be 1.47% (1979: 0.54%). Over 40% of the stones were passed spontaneously. Conclusion: There has been a marked increase in the prevalence and incidence of urolithiasis in Germany within the last 22 years. This probably results from improvements in clinical-diagnostic procedures, changes in nutritional and environmental factors and a general apathy towards metabolic clarification and metaphylaxis.
Gesehen am 11.03.2022